Scheme for improved integration and lifetime for piezoelectric energy harvesters - Elliott,ADT; Dicken,J; Miller,LM; Wright,PK; Mitcheson,PD (2013)
The power output of piezo harvesters can be significantly increased by using charge modification techniques such as piezoelectric pre-biasing or synchronous switched harvesting, but in order to achieve a significant power gain high Q electrical resonant circuits must be used. For integrated systems with a significant size constraint, or in systems using on-chip inductors, achieving high Q can be difficult. Here we present an improved interface circuit which performs better than all previously presented techniques, especially in cases where the Q-factor of the resonant circuit is low. This has the added advantage of extending the useful life of the harvester because repeated cycling reduces the quality of the piezoelectric film, increasing the series resistance and lowering the electrical Q and the performance. Maximum power extraction by this new circuit is also less sensitive to the supply rail voltage than previously presented implementations, which reduces control power overhead.